Gluten-related disorders and schizophrenia- potential linking mechanisms, diagnostic and therapeutic challenge - Tomaka, Joanna; Karakuła-Juchnowicz, Hanna; Morylowska-Topolska, Justyna; Dzikowski, Michał; Juchnowicz, Dariusz; Flis, Marta; Siek, Aleksandra; Próchnicki, Michał (Current Problems of Psychiatry, 2017)
More and more evidence confirms the theory that the intake of cereal products containing gluten may play an important role in the pathogenesis of many diseases. There are also premises indicating the relationship between the so-called gluten-related diseases and the development and course of mental disorders, including schizophrenia.The aim of this article is to review the literature on the potential relationship between the consumption of gluten and schizophrenia, considering the etiopathogenesis and the role of gluten-free diet in the treatment of schizophrenia.Methods: There were analysed available research papers in PubMed and Google Scholar with the key words: schizophrenia, gluten-related disorders, allergy to grain products, celiac disease, microbiota, immune system, exorphins and time span: 1960-2016 .Conclusions: Existing research results indicate a possible relationship between diet rich in grain products with high gluten con-tent and the occurrence or exacerbation of schizophrenia symptoms. However, further studies are necessary to: 1) identify groups of patients for whom the consumption of cereal products (gluten) is associated with a particular risk of schizophrenia exacerbation, 2) determine the mechanisms relating the consumption of gluten with the mental state of schizophrenic patients, 3) get the possible benefits of implementing gluten-free diet in patients with schizophrenia.